New genus and new species of Chauliodinae (Insecta: Megaloptera: Corydalidae) from Brazil - Cardoso-Costa, Gil; de Azevêdo, Carlos Augusto Silva; Ferreira, Nelson Jr. (Zootaxa, 2013)
A new genus and new species of Chauliodinae are described and illustrated, Puri gen. nov. and P. aleca sp. nov. The ma-terial was collected in the Mantiqueira Mountain Range,ItamonteMunicipality,State of Minas Gerais,Brazil. This is the first report of adults of this subfamily fromBrazil. In the male, the new genus is diagnosed by the short subserrate anten-nae, length less than ½ of forewing; wings alternating dark and pale venation; forewings with crossvein between 1A and 2A placed between footstalks of 1A and 2A; hindwings with basal r-m crossvein connected to M by an additional short branch; dorsally, ninth tergum anteriorly truncate; laterally, ventral margin acutely produced; ninth sternum with membra-nous apical process; laterally tenth tergum with proximal margin vertical; tenth gonocoxite with bifurcation indistinct; lateral lobes connected by a broad and feebly sclerotized plate. The female is unknown.